Studi Hubungan Kecepatan Arus dan Life Form Karang di Bangsring Underwater (BUNDER) Banyuwangi - Ricka Aprillita; Oktiyas Muzaky Luthfi (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2019)
Bangsring Underwater is close to the Bali Strait, a coral reef-based tourist spot. Many transplants have been done by the local community or outside the area. Every month monitoring of coral reefs, both transplants, and natural ones. This study uses conventional methods to measure current and Line Intercept Transect (LIT) methods for measuring coral reefs. The results of this study are data tables and documentation of conditions in Bangsring Underwater, both in terms of area and coral reefs. Search results from information flow to the south, many coral reefs. South direction dies by being programmed by algae. As for the north, it was published by sand and coral-like anemones, where clownfish live (Nemo).